Answer:
<h2>L=203 yards</h2><h2>W=52 yards</h2>
Step-by-step explanation:
Step one:
given data
perimeter= 510 yards
let the width be x, width=x
length= (4x-5)-----quadruple mean 4 times
Step two:
the expression for perimeter is
P=2L+2W
510=2(4x-5)+2x
510=8x-10+2x
510+10=8x+2x
520=10x
divide both sides by 10
x=520/10
x=52
the width is 52 yards
the lenght is (4x-5)
L=4(52)-5
L=208-5
L=203 yards
<h2>
Answer:</h2>
<h2>
Step-by-step Explanation;</h2>
![y > 2x \: y \: > \: 3 \: \\ solve \: for \: x \\ x \: € \: ( \frac{3}{2y} \: \frac{1}{2} )\: y > \: 3 \\ solve \: for \: y \\ y \: > \: \frac{3}{2x} \: x \: > \: 0 \: and \: x \: < \: \frac{1}{2}](https://tex.z-dn.net/?f=y%20%20%3E%202x%20%5C%3A%20y%20%5C%3A%20%20%3E%20%20%5C%3A%203%20%5C%3A%20%20%5C%5C%20solve%20%5C%3A%20for%20%5C%3A%20x%20%5C%5C%20x%20%5C%3A%20%E2%82%AC%20%5C%3A%20%28%20%5Cfrac%7B3%7D%7B2y%7D%20%20%5C%3A%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%29%5C%3A%20y%20%3E%20%20%5C%3A%203%20%5C%5C%20solve%20%5C%3A%20for%20%5C%3A%20y%20%5C%5C%20y%20%5C%3A%20%20%3E%20%20%5C%3A%20%20%5Cfrac%7B3%7D%7B2x%7D%20%20%5C%3A%20x%20%5C%3A%20%20%3E%20%20%5C%3A%200%20%5C%3A%20and%20%5C%3A%20x%20%5C%3A%20%20%3C%20%5C%3A%20%20%5Cfrac%7B1%7D%7B2%7D%20)
<h2 />
<h2>HOPE IT HELPS!!!</h2>
<h2>I NEED BRAINLIEST ✌️</h2>
Answer:
Step-by-step explanation:
x = 0.8 + 0.2y
Answer:
ok so here is the answer: n
hk
b
a
х
V
Angle a = 126. What is the measure of angle b? Explain how you calculated your answer.
Angle a = 126 Write an equation(s) in terms of b to find the measure of angle h.
Calculate the measure of angle h, using the equation(s) you wrote for Part B.
How would knowing the measure of angle y change the equation(s) you wrote in Part B to find the measure of angle h?
2021 Muminate Education Inc Your input: factor x2+4x+3.
To factor the quadratic function x2+4x+3, we should solve the corresponding quadratic equation x2+4x+3=0.
Indeed, if x1 and x2 are the roots of the quadratic equation ax2+bx+c=0, then ax2+bx+c=a(x−x1)(x−x2).
Solve the quadratic equation x2+4x+3=0.
The roots are x1=−1, x2=−3 (use the quadratic equation calculator to see the steps).
Therefore, x2+4x+3=1(x+1)(x+3).
(x2+4x+3)=1(x+1)(x+3)
Step-by-step explanation: